Effect of Planting Pattern on Productivity and Water Use Efficiency of Pearl Millet in the Indian Semi-Arid Region - and R.M. Singh, Babloo Sharma, Reena Kumari Pratibha Kumari, Santosh K. Meena (Journal of the Indian Society of Soil Science, 2015)
In the semi-arid regions of India, profitable cropping systems must make efficient use of limited and highly variable precipitation. Hence, new planting patterns (ridge, bed and seeddrill system that act as the in-situ soil moisture conservation) were evaluated for the pearl millet [Pennisetum glaucum (L) r. br] crop during 2009 under semi-arid tropical (SAT) region of India. The broadcast method is commonly used for planting of pearl millet. During the crop growth period (July to October, 2009), total rainfall was 718.5 mm and 21.0% of the total rainfall consisted of the effective rainfall for all plots. Ridge, bed and seeddrill planting patterns increased soil moisture by 37.1, 27.0 and 13.5 per cent, respectively, compared to broadcast pattern in 45 cm depth of root zone. Consequently, grain yield and water use efficiency increased significantly under ridge, bed and seeddrill method of sowing compared to the broadcasting method. Grain yield under ridge pattern increased by 11.6 per cent over broadcast method (1.65 t ha-1). Since rainfall is often below average of ten years (1059 mm), we recommend ridge method of planting for SAT region of India, to mitigate the effect of drought stress and crop failure.